DETERMINAN KEUANGAN INKLUSIF DI SUMATERA UTARA, INDONESIA - Nasution, Lia Nazliana; Sari, Pipit Buana; Dwilita, Handriyani (Jurnal Ekonomi & Studi Pembangunan, 2013)
Abstract: This study is a baseline study that presents an overview of some of the factors that affect the application of policies of inclusive finance in North Sumatra. In this study the authors conducted a descriptive study of the total population, the number of productive population, the number of bank branches in North Sumatra and North Sumatra GRDP in the period 2010 to 2013. It is known that the number of people in North Sumatra in the period of observation has increased, but experienced reduction in the workforce. If seen from the data that reflected the local revenue of the value of GDP then an increase in revenue in North Sumatra, but not too big. While other factors measured were the number of bank branches operating in North Sumatra in the period of the study data showed that there was a significant increase over the number of bank branches operating in North Sumatra. This means that in terms of factors of population, income and branch offices in North Sumatra have been quite supportive of the application and implementation of better towards inclusive finance in North Sumatra.Â Abstrak: Studi ini merupakan kajian dasar yang mennyajikan beberapa gambaran sebagian faktor-faktor yang mempengaruhi penerapan kebijakan inklusif keuangan di Sumatera Utara. Pada studi ini penulis melakukan kajian deskriptif terhadap jumlah penduduk, jumlah penduduk produktif, jumlah kantor cabang bank di Sumatera Utara dan PDRB Sumatera Utara dalam kurun waktu 2010 sampai dengan 2013. Diketahui bahwa jumlah penduduk di Sumatera Utara dalam kurun waktu pengamatan mengalami peningkatan, namun mengalami penurunan jumlah angkatan kerja. Jika dilihat dari data pendapatan daerah yang dicerminkan dari nilai PDRB maka terjadi peningkatan pendapatan di Sumatera Utara, namun tidak terlalu besar. Sedangkan faktor lainnya yang diamati adalah jumlah kantor cabang bank yang beroperasi di Sumatera Utara dalam kurun waktu studi diperoleh data bahwa terjadi peningkatan yang cukup signifikan atas jumlah kantor cabang perbankan yang beroperasi di Sumatera Utara. Ini artinya dari segi faktor jumlah penduduk, pendapatan dan kantor cabang di Sumatera Utara telah cukup mendukung atas penerapan dan pelaksanaan yang lebih baik terhadap keuangan inklusif di Sumatera Utara.Â